Review of the official opponent to a PhD (Law) thesis (major 12.00.08): Buchaev S. M. “Criminological issues of counteracting the process of forming a personality of a terrorist” - A. V. Petryanin (Russian Journal of Economics and Law)
Objective: to conducting a comprehensive analysis of the PhD (Law) thesis by S. M. Buchayev, on the topic “Criminological issues of counteracting the process of forming a personality of a criminal-terrorist”, defended in 2019 in the Dissertation Council D 999.132.02 at Chechen State University and Southwestern State University.Methods: dialectic approach to the cognition of social phenomena, allowing to analyze them in the historical development and functioning in the context of a set of objective and subjective factors, which determined the choice of the following research methods: formal-logical, comparative-legal, sociological.Results: the author’s idea is studied, which is aimed at solving the criminological problems of counteracting the process of formation of a criminal-terrorist personality. The relevance of the research is proved. The most frequently used method of recruitment is highlighted, based on the scenario of social inequality using the Internet telecommunication network. The main provisions representing the author’s concept are confirmed. The reviewer’s views on the thesis are presented, concerning the definition of the characteristics of an individual terrorist, terrorist crimes as a whole, and the system impeding the formation of a criminal-terrorist personality. A number of the thesis provisions are critically evaluated, including its narrow geography, correlation between extremism and terrorism, and the author’s system of terrorist crimes.Scientific novelty: the doctrinal merits of the thesis are identified; the provisions that require additional theoretical and applied reasoning are revealed. In general, the thesis by S. M. Buchayev significantly deepens and expands doctrinal positions on the nature, methods and means of countering the process of a criminal terrorist personality formation.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activities when considering and researching the issues related to the current state of recruitment and the personality of a person committing terrorist crimes.